2015
DOI: 10.1002/tox.22171
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and mitochondrial injury-mediated cytotoxicity induced by silver nanoparticles in human A549 and HepG2 cells

Abstract: The dose-dependent cytotoxicity induced by AgNPs may result from an interaction of oxidative stress, DNA damage and mitochondrial injury in A549 and HepG2 cells. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 1691-1699, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…Our results agree with HepG2 [34][35][36][37][38][39][40][41]43] and lymphocytes [21] literature data: the toxicity is strictly dependent on amount of NPs/cell.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results agree with HepG2 [34][35][36][37][38][39][40][41]43] and lymphocytes [21] literature data: the toxicity is strictly dependent on amount of NPs/cell.…”
Section: Discussionsupporting
confidence: 91%
“…We speculate that probably generation of ROS in HepG2 cells is dependent on imbalance of homeostasis of glycans metabolism, as demonstrated for glucose [44,45]. The results of our study contradict the conclusion of other reports [14,34,39,40,43], suggesting the generation of ROS upon AgNPs treatment.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…In vitro cytotoxicity studies are often used to characterize the biological response to AgNPs, and the results of these studies may be used to identify hazards associated with exposure to AgNPs. Some important studies that have shown the toxic effects of AgNPs on different cell lines, including macrophages (RAW 264.7), including bronchial epithelial cells (BEAS-2B), alveolar epithelial cells (A549), hepatocytes (C3A, HepG2), colon cells (Caco2), skin keratinocytes (HaCaT), human epidermal keratinocytes (HEKs), erythrocytes, neuroblastoma cells, embryonic kidney cells (HEK293T), porcine kidney cells (Pk 15), monocytic cells (THP-1), and stem cells [20,[108][109][110][111][112][113][114][115][116][117], are discussed below.…”
Section: In Vitro Effectsmentioning
confidence: 99%